2021
DOI: 10.1111/pce.13962
|View full text |Cite
|
Sign up to set email alerts
|

Bioenergy sorghum maintains photosynthetic capacity in elevated ozone concentrations

Abstract: Elevated tropospheric ozone concentration (O3) significantly reduces photosynthesis and productivity in several C4 crops including maize, switchgrass and sugarcane. However, it is unknown how O3 affects plant growth, development and productivity in sorghum (Sorghum bicolor L.), an emerging C4 bioenergy crop. Here, we investigated the effects of elevated O3 on photosynthesis, biomass and nutrient composition of a number of sorghum genotypes over two seasons in the field using free‐air concentration enrichment (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 87 publications
7
18
0
Order By: Relevance
“…This sits between parameter estimates previously published for maize grown in controlled environment conditions (m = 3.06, Ball 1988;m = 3.23, Collatz et al, 1992;m = 4.53, Miner and Bauerle 2017;g1 = 1.281;Yun et al, 2020) and very close to a parameter estimate for maize in the field in Colorado (m = 3.72, Miner and Bauerle 2017). The results are also comparable to measurements of Panicum virgatum (m = 3.9), Miscanthus x giganteus (m = 3.3) and Sorghum bicolor (m = 4.32) grown at nearby field sites (LeBauer et al, 2013;Li et al, 2021) as well as C4 grasses in general (m = 4.1, Miner et al, 2017;m = 4.0, Franks et al, 2017). But, relatively subtle variation in gsmodel parameters can significantly impact predictions of leaf, canopy, ecosystem and global water fluxes (Franks et al, 2017;Wolz et al, 2017), so additional data collection is still needed.…”
Section: Discussionsupporting
confidence: 84%
“…This sits between parameter estimates previously published for maize grown in controlled environment conditions (m = 3.06, Ball 1988;m = 3.23, Collatz et al, 1992;m = 4.53, Miner and Bauerle 2017;g1 = 1.281;Yun et al, 2020) and very close to a parameter estimate for maize in the field in Colorado (m = 3.72, Miner and Bauerle 2017). The results are also comparable to measurements of Panicum virgatum (m = 3.9), Miscanthus x giganteus (m = 3.3) and Sorghum bicolor (m = 4.32) grown at nearby field sites (LeBauer et al, 2013;Li et al, 2021) as well as C4 grasses in general (m = 4.1, Miner et al, 2017;m = 4.0, Franks et al, 2017). But, relatively subtle variation in gsmodel parameters can significantly impact predictions of leaf, canopy, ecosystem and global water fluxes (Franks et al, 2017;Wolz et al, 2017), so additional data collection is still needed.…”
Section: Discussionsupporting
confidence: 84%
“…Research from SoyFACE showed elevated O 3 concentrations (approximately 100 ppb) significantly reduced leaf photosynthetic capacity in maize (Choquette et al, 2019(Choquette et al, , 2020Sorgini et al, 2019;Wedow et al, 2021b;Yendrek et al, 2017a,b), but had little or no effect on photosynthesis and biomass yield in switchgrass (Li et al, 2019a) and sorghum (Li et al, 2021). These studies also reported considerable genotypic variation in O 3 sensitivity among maize and sorghum lines (Choquette et al, 2019;Li et al, 2021;Yendrek et al, 2017a,b). In a study at the FO 3 X facility, Moura et al (2018) exposed two potted sugarcane genotypes to three levels of O 3 concentrations and found a significant reduction in plant biomass at increased [O 3 ].…”
Section: Lessons Learned From Face Experiments C 3 Versus Cmentioning
confidence: 95%
“…More recent experiments at SoyFACE have tested the response of maize (Choquette et al, 2019(Choquette et al, , 2020Yendrek et al, 2017aYendrek et al, , 2017b and other C 4 plants, specifically sorghum and switchgrass (Li et al, 2019a(Li et al, , 2021, to a step increase in elevated [O 3 ] (100 ppb). Yendrek et al (2017a,b) grew over 200 inbred and hybrid maize lines from 2013-2015 and directly measured and modeled multiple leaf traits including instantaneous gas exchange (A and g s ), the rate limiting steps of C 4 photosynthesis (V pmax and V max ), chlorophyll content, specific leaf area, and leaf nitrogen content.…”
Section: Soyfacementioning
confidence: 99%
“…The light response curve shows a linear increase in photosynthetic response up to a light intensity of about 500 μmol photon/m 2 /s with a slope of 0.064 mol CO 2 /mol photon and the dark respiration intersect of the linear was determined to be at −2.6 μmol CO 2 /m 2 /s. In another study evaluating five sorghum genotypes under field-grown conditions, respiration rates of dark-adapted leaves were on average 1.4 μmol CO 2 /m 2 /s ( Li et al, 2021 ). We therefore consider the dark respiration intersect of 2.6 μmol CO 2 /m 2 /s to represent a rather conservative estimate.…”
Section: Methodsmentioning
confidence: 99%